Antibiotic Resistance Patterns of Salmonella and Escherichia Coli in the Groundwater of Cyprus - Economides, Constantinos; Liapi, Maria; Makris, Konstantinos C. (My University, 2012)
In addition to diet-based vectors of disease, the contribution of water-borne zoonotic agents to gastrointestinal illnesses may be significant, but this has yet to be investigated for Cyprus. Our main objective was to evaluate antibiotic resistance patterns of Salmonella and Escherichiacoli in groundwater samples collected at confined animal feeding operations. This is the first report on the occurrence of antibiotic-resistant Salmonella and E. coli strains in the groundwater of Cyprus. Most of Salmonella isolates belonged to the subgroup enterica, whereas none of the E. coli isolates expressed the verotoxin-encoding gene. Out of 27 isolated Salmonella strains, nearly half of them were resistant to at least one or more antibiotic, whereas the highest resistance was exhibited by sulphamethoxazole (85%), followed by streptomycin (39%), and tetracycline (31%). For the E. coli isolates, nearly a third of them showed resistance to at least one antibiotic, whereas the selection of antibiotic resistance was equal among sulphamethoxazole, tetracycline and streptomycin (20%). This study demonstrated that Salmonella and E. coli in groundwater could pose a public health risk via oral ingestion of contaminated water. Best management practices are needed for overexploited groundwater supplies of rural areas, minimizing human exposure to antibiotic-resistant pathogens.
Keywords: Antiinfective agent; Bacterial protein; Groundwater; Antibiotic resistance; Disease vector; Bacterium; Health risk; Pathogen; Animal husbandry; Bacterium identification; Drug effect; Escherichia coli; Isolation and purification; Metabolism; Microbial sensitivity test; Microbiology; Multidrug resistance; Polymerase chain reaction; Salmonella; Anti-bacterial agents; Bacterial proteins; Bacterial typing techniques; Colony count; Microbial; Bacterial count; Drug resistance; Bacterial; Escherichia coli; Animalia